Program Mathematics Ethnic Learning untuk Meningkatan Minat Belajar Matematika Siswa SDN 1 Kauman - Wibowo, Sigit; Anggraini, Sandra Prilia; Sunaryo, Sunaryo; Sugevin, Wecya; Nirwana, Rima Cahya; Yuniawatika, Yuniawatika (Universitas Nusantara PGRI Kediri, 2022)
This service aims to increase interest in mathematics by linking traditional games with learning mathematics. The subjects in this service are students in grades 4, 5 and 6 at SDN 1 Kauman for the academic year 2021/2022. This service is collaborative between the service team, class teachers, and school principals. In this service activity using the SP4E method which includes: (1) Socialization and coordination, (2) Material preparation, (3) Training and Exploration, (4) Direction and Guidance, (5) Application, (6) Evaluation and Reflection. Based on the results of the pretest and postest that have been carried out, it shows that there is an increase in math scores in grades 4, 5 and 6, which initially only 8% of students who got math scores above the KKM but after learning using traditional games the percentage of students who got math scores above the KKM increased. that is equal to 71% of students.